PENGEMBANGAN BAHAN AJAR TEMATIK TERPADU BERBASIS MODEL PROBLEM BASED LEARNING DI KELAS IV SEKOLAH DASAR - Silviana Nasrul (Universitas Negeri Padang, 2018)
This research is motivated importance of developing an integrated thematic teaching materials that can increase a student's progress in learning .. To overcome these problems it is necessary to find a solution in the form of the development of teaching . This solution is realized in the form of developing an integrated thematic teaching on problem based learning model is valid , practical , and effective . Designed teaching materials is a book teacher and student books .This type of research is the development of research using a model 4-D: the definition define, design, developing and disseminate. The results obtained, validation of lesson plan gained an average of 3.6 in the category of very valid. Validation of teaching materials gained an average of 3.8 with very valid category. At this stage of the practicalities, the result that has practical teaching materials to be used. The use of integrated thematic teaching materials can enhance the activity and student learning outcomes. The student’s learning achievement reached 78,6%. The research finding shows that the integrated thematic teacher material is valid, practical, and effective to be used as one of the teaching materials in the fourth grade of elementary school. Keywords: Integrated Thematic Teaching Materials, Problem Based Learning ModelThis research is motivated importance of developing an integrated thematic teaching materials that can increase a student's progress in learning .. To overcome these problems it is necessary to find a solution in the form of the development of teaching . This solution is realized in the form of developing an integrated thematic teaching on problem based learning model is valid , practical , and effective . Designed teaching materials is a book teacher and student books .This type of research is the development of research using a model 4-D: the definition define, design, developing and disseminate. The results obtained, validation of lesson plan gained an average of 3.6 in the category of very valid. Validation of teaching materials gained an average of 3.8 with very valid category. At this stage of the practicalities, the result that has practical teaching materials to be used. The use of integrated thematic teaching materials can enhance the activity and student learning outcomes. The student’s learning achievement reached 78,6%. The research finding shows that the integrated thematic teacher material is valid, practical, and effective to be used as one of the teaching materials in the fourth grade of elementary school. Keywords: Integrated Thematic Teaching Materials, Problem Based Learning Model